Automatic generation of language-based tools using the LISA system - Henriques, Pedro Rangel (2005)
Many tools have been constructed using different formal methods to process various parts of a language specification (e.g. scanner generators, parser generators and compiler generators). The automatic generation of a complete compiler was the primary goal of such systems, but researchers recognised the possibility that many other language-based tools could be generated from formal language specifications. Such tools can be generated automatically whenever they can be described by a generic fixed part that traverses the appropriate data structures generated by a specific variable part, which can be systematically derivable from the language specifications. The paper identifies generic and specific parts for various language-based tools. Several language-based tools are presented in the paper, which are automatically generated using an attribute grammar-based compiler generator called LISA. The generated tools that are described in the paper include editors, inspectors, debuggers and visualisers/animators. Because of their complexity of construction, special emphasis is given to visualisers/animators, and the unique contribution of our approach toward generating such tools.